Impact of a phytogenic feed additive on growth performance, feed intake, and carcass traits of finishing steers. Issue 4 (27th July 2019) - Brand, Tassilo; Hünerberg, Martin; McAllister, Tim A; He, Maolong; Saleem, Atef M; Shen, Yizhao; Miller, Bryan; Yang, Wenzhu
Abstact: The purpose of this study was to evaluate the effect of a phytogenic feed additive (Digestarom [DA]; Biomin, Getzersdorf, Austria) on growth performance, feed intake, carcass traits, fatty acid composition, and liver abscesses of finishing steers. One hundred twenty Angus × Charolais crossbred steers (488 ± 26.5 kg) were used in a 110-d feeding experiment. Steers were blocked by weight and randomly assigned to 12 pens with 10 steers per pen. Each pen was allocated to one of three diets. Each diet contained 86.5% barley, 10.0% barley silage, and 3.5% vitamin and mineral supplement on a dry matter (DM) basis. The diets contained 0, 0.05, and 0.1 g DA/kg complete diet (DM basis), to achieve average daily DA intakes of 0 (control), 0.5 (LowDA), and 1.0 g (HighDA) per steer. Diets were prepared once daily and provided ad libitum. Two pens per treatment were equipped to record individual feed intake behavior. Steers were weighed every 28 d and carcass traits and liver scores were recorded at slaughter. Dry matter intake (average: 9.34 kg/d) did not differ ( P > 0.05) among diets. Average daily gain tended to increase linearly as DA increased (control: 1.82; LowDA: 1.87; and HighDA: 1.95 kg/d; P < 0.09), but gain:feed ratio was not affected. Supplementation of DA affected longissimus muscle area quadratically ( P = 0.05) with the largest area observed for LowDA. However, dressing percentage decreased linearly in response to increasing level of DA ( P < 0.01). Total abscessed livers were not affected, whereas proportion of severe liver abscesses was numerically lower with DA (30.8% and 42.5% for LowDA and HighDA) compared to the control (50%).